RECLAIMING EPISTEMIC UNITY THROUGH INTEGRATIVE SCIENTIFIC EDUCATION IN BEDIÜZZAMAN SAID NURSI’S MEDRESETÜ’Z-ZEHRA - Purwaningtyas, Dhita Ayomi (State Islamic University of Datokarama Palu, 2025)
This article explores Bediüzzaman Said Nursi’s vision of Medresetü’z-Zehra as a paradigm of integrative scientific education rooted in Islamic metaphysics and decolonial epistemology. Situated in the intellectual and political turmoil of late Ottoman and early Republican Turkey, Nursi’s educational proposal responds to the epistemic rupture caused by the secular-religious dualism imposed by Western modernity. Based on Syed Muhammad Naquib al-Attas’s theory of Islamization of knowledge and Edward Said’s critique of Western epistemic dominance, the article situates Medresetü’z-Zehra as a theological and postcolonial intervention. The research method used was qualitative with a hermeneutic approach. The results showed that Nursi’s educational model repositions scientific knowledge, especially rational and empirical disciplines, as spiritually meaningful when integrated with religious and humanistic sciences under the ontological unity of tawḥīd, seeking to produce scholars (ʿālim-rabbānī) who are intellectually integrated, morally anchored, and spiritually awakened. The analysis shows that Medresetü’z-Zehra is historically significant and remains a vital reference point for contemporary Islamic educational reform amid ongoing crises of identity, ethics, and epistemological fragmentation